A trading strategy with dual-beta estimates. Issue 5 (21st February 2022) - Chong, James
Abstract : Purpose: The purpose of this paper is to adopt a trading strategy using upside and downside beta estimates. Design/methodology/approach: With daily data from April 30, 1997 to April 30, 2021, the author utilizes the dual-beta model when estimating upside and downside betas, in constructing and rebalancing a portfolio from a buy list of Dow Jones Industrial Average component stocks. Benchmarks include the S&P 500 Total Return index, Invesco S&P 500 Low Volatility ETF (SPLV) and iShares MSCI USA Min Vol Factor ETF (USMV). The dual-beta portfolio performance is assessed by economic cycles and by the Fama-French five-factor model. Findings: The dual-beta portfolio outperforms the benchmarks for the whole period under study as well as the majority of sub-periods. It is the only strategy with a statistically positive and economically significant risk-adjusted return. Originality/value: The author offers a simple stock trading strategy for generating wealth.